Heteroclinic dynamics in network dynamical systems with higher-order interactions - Bick, Christian; von der Gracht, Sören (Journal of Complex Networks)
Heteroclinic structures organize global features of dynamical systems. We analyse whether heteroclinic structures can arise in network dynamics with higher-order interactions which describe the nonlinear interactions between three or more units. We find that while commonly analysed model equations such as network dynamics on undirected hypergraphs may be useful to describe local dynamics such as cluster synchronization, they give rise to obstructions that allow to design of heteroclinic structures in phase space. By contrast, directed hypergraphs break the homogeneity and lead to vector fields that support heteroclinic structures.
Keywords: Applied Mathematics; Computational Mathematics; Control and Optimization; Management Science and Operations Research; Computer Networks and Communications

Evaluating Security Through Isolation and Defense in Depth - Bodden, Eric; Pottebaum, Jens; Fockel, Markus; Gräßler, Iris (IEEE Security & Privacy)
Keywords: Law; Electrical and Electronic Engineering; Computer Networks and Communications

Methodology for Certification-Compliant Effect-Chain Modeling - Gräßler, Iris; Wiechel, Dominik; Koch, Anna-Sophie; Sturm, Tim; Markfelder, Thomas (Systems)
The success of engineering complex technical systems is determined by meeting customer requirements and institutional regulations. One example relevant to the automobile industry is the United Nations Economic Commission of Europe (UN ECE), which specifies the homologation of automobile series and requires proof of traceability. The required traceability can be achieved by modeling system artifacts and their relations in a consistent, seamless model—an effect-chain model. Currently, no in-depth methodology exists to support engineers in developing certification-compliant effect-chain models. For this purpose, a new methodology for certification-compliant effect-chain modeling was developed, which includes extensions of an existing method, suitable models, and tools to support engineers in the modeling process. For evaluation purposes, applicability is proven based on the experience of more than 300 workshops at an automotive OEM and an automotive supplier. The following case example is chosen to demonstrate applicability: the development of a window lifter that has to meet the demands of UN ECE Regulations R156 and R21. Results indicate multiple benefits in supporting engineers with the certification-compliant modeling of effect chains. Three benefits are goal-oriented modeling to reduce the necessary modeling capacity, increasing model quality by applying information quality criteria, and the potential to reduce costs through automatable effect-chain analyses for technical changes. Further, companies in the automotive and other industries will benefit from increased modeling capabilities that can be used for architecture modeling and to comply with other regulations such as ASPICE or ISO 26262.
Keywords: Information Systems and Management; Computer Networks and Communications; Modeling and Simulation; Control and Systems Engineering; Software

The potential of digital nudging to bridge the gap between environmental attitude and behavior in the usage of smart home applications - Stieglitz, Stefan; Mirbabaie, Milad; Deubel, Annika; Braun, Lea-Marie; Kissmer, Tobias (International Journal of Information Management)
Keywords: Library and Information Sciences; Computer Networks and Communications; Information Systems

Lessons Learned from the Introduction of Systems Engineering - Wilke, Daria; Grothe, Robin; Bretz, Lukas; Anacker, Harald; Dumitrescu, Roman (Systems)
The introduction of Systems Engineering is an approach for dealing with the increasing complexity of products and their associated product development. Several introduction strategies are available in the literature; nevertheless, the introduction of Systems Engineering into practice still poses a great challenge to companies. Many companies have already gained experience in the introduction of Systems Engineering. Therefore, as part of the SE4OWL research project, the need to conduct a study including expert interviews and to collect the experiences of experts was identified. A total of 78 hypotheses were identified from 13 expert interviews concerning the lessons learned. Using exclusion criteria, 52 hypotheses were validated in a subsequent quantitative survey with 112 participants. Of these 52 hypotheses, 40 could be confirmed based on the survey results. Only four hypotheses were rejected, and eight could neither be confirmed nor rejected. Through this research, guidance is provided to companies to leverage best practices for the introduction of their own Systems Engineering and to avoid the poor practices of other companies.
Keywords: Information Systems and Management; Computer Networks and Communications; Modeling and Simulation; Control and Systems Engineering; Software

EEG Correlates of Distractions and Hesitations in Human–Robot Interaction: A LabLinking Pilot Study - Richter, Birte; Putze, Felix; Ivucic, Gabriel; Brandt, Mara; Schütze, Christian; Reisenhofer, Rafael; Wrede, Britta; Schultz, Tanja (Multimodal Technologies and Interaction)
In this paper, we investigate the effect of distractions and hesitations as a scaffolding strategy. Recent research points to the potential beneficial effects of a speaker’s hesitations on the listeners’ comprehension of utterances, although results from studies on this issue indicate that humans do not make strategic use of them. The role of hesitations and their communicative function in human-human interaction is a much-discussed topic in current research. To better understand the underlying cognitive processes, we developed a human–robot interaction (HRI) setup that allows the measurement of the electroencephalogram (EEG) signals of a human participant while interacting with a robot. We thereby address the research question of whether we find effects on single-trial EEG based on the distraction and the corresponding robot’s hesitation scaffolding strategy. To carry out the experiments, we leverage our LabLinking method, which enables interdisciplinary joint research between remote labs. This study could not have been conducted without LabLinking, as the two involved labs needed to combine their individual expertise and equipment to achieve the goal together. The results of our study indicate that the EEG correlates in the distracted condition are different from the baseline condition without distractions. Furthermore, we could differentiate the EEG correlates of distraction with and without a hesitation scaffolding strategy. This proof-of-concept study shows that LabLinking makes it possible to conduct collaborative HRI studies in remote laboratories and lays the first foundation for more in-depth research into robotic scaffolding strategies.
Keywords: Computer Networks and Communications; Computer Science Applications; Human-Computer Interaction; Neuroscience (miscellaneous)

Workarounds as generative mechanisms for bottom‐up process innovation—Insights from a multiple case study - Bartelheimer, Christian; Wolf, Verena; Beverungen, Daniel (Information Systems Journal)
Abstract Workarounds are goal‐driven deviations from the standard operating procedures performed to overcome obstacles constraining day‐to‐day work. Despite starting as temporary fixes, they can become established across an organisation and trigger the innovation of processes and IT artefacts that can resolve misfits permanently. Although prior research has elicited antecedents and types of workarounds, it is not known how workarounds diffuse in an organisation and, thereby, innovating co‐workers' activities, IT artefacts, and organisational structures. The results of our multiple two‐year case study provide unique empirical insights into the diffusion of workarounds and how they can act as generative mechanisms for bottom‐up process innovation.
Keywords: Computer Networks and Communications; Information Systems; Software

Seizing the Opportunity for Automation—How Traffic Density Determines Truck Drivers' Use of Cruise Control - Hoffmann, Christin; Thommes, Kirsten (IEEE Transactions on Human-Machine Systems)
Keywords: Artificial Intelligence; Computer Networks and Communications; Computer Science Applications; Human-Computer Interaction; Signal Processing; Control and Systems Engineering; Human Factors and Ergonomics

Opto-electronic bias of a superconducting nanowire single photon detector using a cryogenic photodiode - Thiele, Frederik; Hummel, Thomas; Protte, Maximilian; Bartley, Tim (APL Photonics)
Superconducting Nanowire Single Photon Detectors (SNSPDs) have become an integral part of quantum optics in recent years because of their high performance in single photon detection. We present a method to replace the electrical input by supplying the required bias current via the photocurrent of a photodiode situated on the cold stage of the cryostat. Light is guided to the bias photodiode through an optical fiber, which enables a lower thermal conduction and galvanic isolation between room temperature and the cold stage. We show that an off-the-shelf InGaAs–InP photodiode exhibits a responsivity of at least 0.55 A/W at 0.8 K. Using this device to bias an SNSPD, we characterize the count rate dependent on the optical power incident on the photodiode. This configuration of the SNSPD and photodiode shows an expected plateau in the single photon count rate with an optical bias power on the photodiode above 6.8 µW. Furthermore, we compare the same detector under both optical and electrical bias, and show there is no significant changes in performance. This has the advantage of avoiding an electrical input cable, which reduces the latent heat load by a factor of 100 and, in principle, allows for low loss RF current supply at the cold stage.
Keywords: Computer Networks and Communications; Atomic and Molecular Physics; and Optics

How crises are different - Design principles for conversational agents to support Emergency Management Agencies - Stieglitz, Stefan; Hofeditz, Lennart; Brünker, Felix; Ehnis, Christian; Mirbabaie, Milad; Ross, Björn (International Journal of Information Management)
Keywords: Library and Information Sciences; Computer Networks and Communications; Information Systems

Towards electronic structure-based ab-initio molecular dynamics simulations with hundreds of millions of atoms - Schade, Robert; Kenter, Tobias; Elgabarty, Hossam; Lass, Michael; Schütt, Ole; Lazzaro, Alfio; Pabst, Hans; Mohr, Stephan; Hutter, Jürg; Kühne, Thomas; Plessl, Christian (Parallel Computing)
Keywords: Artificial Intelligence; Computer Graphics and Computer-Aided Design; Computer Networks and Communications; Hardware and Architecture; Theoretical Computer Science; Software

Rate Splitting in MIMO RIS-Assisted Systems With Hardware Impairments and Improper Signaling - Soleymani, Mohammad; Santamaria, Ignacio; Jorswieck, Eduard A. (IEEE Transactions on Vehicular Technology)
Keywords: Electrical and Electronic Engineering; Computer Networks and Communications; Aerospace Engineering; Automotive Engineering

Improper Signaling for Multicell MIMO RIS-Assisted Broadcast Channels With I/Q Imbalance - Soleymani, Mohammad; Santamaria, Ignacio; Schreier, Peter J. (IEEE Transactions on Green Communications and Networking)
Keywords: Computer Networks and Communications; Renewable Energy; Sustainability and the Environment

Collaborating with Virtual Assistants in Organizations: Analyzing Social Loafing Tendencies and Responsibility Attribution - Stieglitz, Stefan; Mirbabaie, Milad; Möllmann, Nicholas R. J.; Rzyski, Jannik (Information Systems Frontiers)
Abstract Organizations increasingly introduce collaborative technologies in form of virtual assistants (VAs) to save valuable resources, especially when employees are assisted with work-related tasks. However, the effect of VAs on virtual teams and collaboration remains uncertain, particularly whether employees show social loafing (SL) tendencies, i.e., applying less effort for collective tasks compared to working alone. While extant research indicates that VAs collaboratively working in teams exert greater results, less is known about SL in virtual collaboration and how responsibility attribution alters. An online experiment with N = 102 was conducted in which participants were assisted by a VA in solving a task. The results indicate SL tendencies in virtual collaboration with VAs and that participants tend to cede responsibility to the VA. This study makes a first foray and extends the information systems (IS) literature by analyzing SL and responsibility attribution thus updates our knowledge on virtual collaboration with VAs.
Keywords: Computer Networks and Communications; Information Systems; Theoretical Computer Science; Software

Improper Gaussian Signaling for the $K$-User MIMO Interference Channels With Hardware Impairments - Soleymani, Mohammad; Santamaria, Ignacio; Schreier, Peter J. (IEEE Transactions on Vehicular Technology)
Keywords: Electrical and Electronic Engineering; Computer Networks and Communications; Aerospace Engineering; Automotive Engineering

Achieving beyond-100-GHz large-signal modulation bandwidth in hybrid silicon photonics Mach Zehnder modulators using thin film lithium niobate - Wang, Xiaoxi; Weigel, Peter O.; Zhao, Jie; Rüsing, Michael; Mookherjea, Shayan (APL Photonics)
Mach-Zehnder electro-optic modulators (EOM) based on thin-film lithium niobate bonded to a silicon photonic waveguide circuit have been shown to achieve very high modulation bandwidths. Open eye-diagram measurements made in the time domain of beyond-small-signal modulation are used to support the modulation-sideband measurements in showing that such EOM’s can support high-frequency modulations well beyond 100 GHz.
Keywords: Computer Networks and Communications; Atomic and Molecular Physics; and Optics

Answering Fuzzy Conjunctive Queries Over Finitely Valued Fuzzy Ontologies - Borgwardt, Stefan; Mailis, Theofilos; Peñaloza, Rafael; Turhan, Anni-Yasmin (Journal on Data Semantics)
Keywords: Artificial Intelligence; Computer Networks and Communications; Information Systems

Answering Fuzzy Conjunctive Queries Over Finitely Valued Fuzzy Ontologies - Borgwardt, Stefan; Mailis, Theofilos; Peñaloza, Rafael; Turhan, Anni-Yasmin (Journal on Data Semantics)
Keywords: Artificial Intelligence; Computer Networks and Communications; Information Systems

Near-field measurement of stochastic electromagnetic fields - Russer, Johannes A.; Uddin, Nasir; Awny, Ahmed Sanaa; Thiede, Andreas; Russer, Peter (IEEE Electromagnetic Compatibility Magazine)
Keywords: Electrical and Electronic Engineering; Computer Networks and Communications; Instrumentation; Signal Processing; Software

Flexible Electronics: Integration Processes for Organic and Inorganic Semiconductor-Based Thin-Film Transistors - Vidor, Fábio; Meyers, Thorsten; Hilleringmann, Ulrich (Electronics)
Keywords: Electrical and Electronic Engineering; Computer Networks and Communications; Hardware and Architecture; Signal Processing; Control and Systems Engineering